Dive! : a book of deep sea creatures - Berger, Melvin (New York : Scholastic, 2000)
Uses a submarine trip to the bottom of the sea to introduce various deep-sea creatures, including the angler fish, octopus, and sperm whale.
Keywords: Deep-sea animals -- Juvenile literature; Marine animals